Metal-accumulating capacity and antioxidant activity of Pylaisia polyantha (Hedw.) Schimp. moss in urban areas - Polishchuk, Oleksandr; Zhylishchych, Yustyna; Antonyak, Halyna (Bìologìčnì studìï, 2023)
Background. Bryophytes, including mosses, are widely used in biomonitoring of atmospheric pollution due to their ability to accumulate metals from atmospheric air. However, the effects of metal accumulation on metabolic processes in bryophyte cells have not been thoroughly studied. The aim of this work was to analyse the accumulation of heavy metals, indices of lipid peroxidation (LPO), and antioxidant status in gametophytes of the epiphytic moss Pylaisia polyantha (Hedw.) Schimp. collected from urban areas with different levels of technogenic load. Materials and Methods. The study was conducted in the city of Lviv (western part of Ukraine). Within the city, 15 sampling sites were selected and grouped as follows: the green zone (A) conditionally used as the control, zone influenced by transport activities (B) and the industrial zone (C). In gametophyte shoots of P. polyantha, concentrations of heavy metals (Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) were analysed using the method of atomic absorption spectrophotometry; the content of LPO products (lipid hydroperoxides, thiobarbituric acid reactive substances (TBARS)) and the activities of antioxidant system enzymes (superoxide dismutase, catalase, glutathione S-transferase) were analysed using standard methods. The results were processed using standard statistical methods. Results. Concentrations of heavy metals in P. polyantha gametophytes collected from the study area can be arranged in descending order as follows: Fe> Mn> Zn> Pb> Cu> Ni> Cr> Co> Cd. The content of individual metals in moss material varied depending on the sampling site. Moss shoots collected from zone B accumulated significantly higher levels of Cd, Co, Cu, Fe, Mn, Pb and Zn, and shoots from zone C had higher levels of Cr and Zn compared to those from the green zone. Moss gametophytes collected from sites in zone B had higher concentrations of LPO products and increased levels of antioxidant enzymes activity compared to the control. Conclusions. Elevated concentrations of heavy metals in moss material from sites exposed to traffic and industrial activities reflect atmospheric heavy metal pollution in urban areas. Intensive accumulation of heavy metals in gametophytes of P. polyantha that grows in the areas of transport activities is accompanied by increased lipid peroxidation processes and activation of enzymes of the antioxidant system in moss cells. Activation of antioxidant enzymes may play an important role in the adaptation of the moss P. polyantha to urban environments contaminated with heavy metals as a result of anthropogenic activities.